2014
DOI: 10.7314/apjcp.2014.15.19.8469
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Prognostic Significance of SOCS-1 Expression in Colorectal Adenocarcinomas

Abstract: Introduction: Recent studies have indicated that down-regulation of the suppressor of cytokine signaling-1 (SOCS-1) gene results in tumor formation and that SOCS-1 acts as a tumor suppressor gene. SOCS-1 has been also suggested to function as a tumor suppressor with colorectal cancer. Objectives: In the present study, we aimed to determine the association of SOCS-1 expression in colorectal cancer tissues with clinicopathologic characteristics immunohistochemically and also to identify its prognostic significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…Nonetheless, low SOCS1 expression in cancer specimens showed a weak but significant correlation with lymph node and distant metastasis, and tumour stages of the disease ( Table 1 ). However, in line with Ayyildiz et al previous report 23 , our analyses failed to reveal a positive correlation between high SOCS1 mRNA levels in CRC tumours and better overall patient survival, even upon CRC patient stratification according to stages ( Fig. 1E ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Nonetheless, low SOCS1 expression in cancer specimens showed a weak but significant correlation with lymph node and distant metastasis, and tumour stages of the disease ( Table 1 ). However, in line with Ayyildiz et al previous report 23 , our analyses failed to reveal a positive correlation between high SOCS1 mRNA levels in CRC tumours and better overall patient survival, even upon CRC patient stratification according to stages ( Fig. 1E ).…”
Section: Discussionsupporting
confidence: 88%
“…Nonetheless, high SOCS1 protein level was still noted in 63% of advanced stage IV CRC tumours. Likewise, Ayyildiz et al observed positive expression of SOCS1 in CRC tissues in nearly half of the cases by immunohistological analysis, but no association between SOCS1 protein level and clinicopathologic tumour characteristics 23 . Conflicting with a dominant tumour suppressor role for SOCS1 in CRC, elevated SOCS1 protein levels in CRC tumours did not predict better patient survival 23 .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Metastasis is a major cause for CRC-related deaths, including liver metastasis and lymph node metastasis [5,6]. Currently, treatments for CRC mainly consist of surgical resection, radiotherapy and chemotherapy [7]. What is more, a series of clinical examinations have been used for CRC screening, such as colonoscopy, fecal occult blood test and sigmoidoscopy [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…All 40 genes, however, did not affect prognosis in patients with TP53 mutant cancer (Figure 6B , Supplementary Figure 1 ), demonstrating a dependence on TP53 mutational status. The genes selected using this method included NCOA3 [ 34 , 35 ], HOXA1 [ 36 ], FOLR1 [ 37 ], SOCS1 [ 38 ], and PIK4CA [ 39 ], which showed similar expression patterns related to survival in patients with cancer. This result suggested that our method was a relatively simple method for identification of genes functionally associated with the p53 pathway.…”
Section: Discussionmentioning
confidence: 99%